HEALTH INEQUALITIES IN CONTEMPORARY PUBLIC HEALTH SYSTEMS: STRUCTURAL AND SOCIOECONOMIC PERSPECTIVES - Chodkowska, Agata; Cieślak, Natalia; Cyrkler, Aleksandra; Czyżak, Kamila; Marzec, Urszula; Dąbek, Karol; Rajca, Eliza; Giza, Agnieszka; Giza, Paulina; Wymoczył, Karolina (International Journal of Innovative Technologies in Social Science, 2026)
Health inequalities remain a persistent challenge in contemporary public health systems, reflecting structural, socioeconomic, and demographic disparities across populations. The aim of this study was to synthesize theoretical frameworks, measurement approaches, epidemiological patterns, and systemic determinants of health inequalities, with particular attention to healthcare access, age-related disparities, seasonal and crisis-related barriers, and mental health inequalities. A narrative review methodology draws on peer-reviewed literature, epidemiological studies, and international health reports published between 2005 and 2025. The analysis integrates major theoretical perspectives, including social causation and health selection hypotheses, and examines commonly applied indicators of socioeconomic status and population health. The findings suggest that health inequalities are multidimensional and arise from the interaction of socioeconomic position, education, employment conditions, geographic distribution of services, and structural barriers embedded within healthcare systems. Vulnerable populations—including children, older adults, migrants, and low-income groups—experience disproportionate exposure to many factors shaping healthcare inequalities. Seasonal disruptions, economic crises, and public health emergencies further exacerbate disparities in healthcare access and continuity of care. Mental health inequalities, increasingly influenced by digital environments, represent an emerging dimension of structural disadvantage. The study concludes that reducing health inequalities requires coordinated multi-level strategies integrating clinical interventions, public policy reforms, and structural improvements in healthcare access. Addressing social determinants remains essential for achieving equitable and sustainable health systems.